Predictores neuropsicológicos de las habilidades académicas. - Ramírez Benítez, Yaser (Panamerican Journal of Neuropsychology / Cuadernos de Neuropsicología, 2014)
The emergent tendency development neuroscience is to comprise predict component cognitive to academic skill. Longitudinal study allowed apply neuropsychological battery Initial Luria from preschool children (6 year old) (ill / control) afterward 5 year old (11 year old) estimates academic (math / reading) and intellectual skill. Study developed Vocabulary, naming rapid and fluid task are predicts school final stage. Observed lexical strategies is predict main spanish idiom from phonological strategies, if children begging phonological strategies without big alteration. Antecedent math skills are amount compare capacity and calculation plain preschool year. Arithmetic capacities to automating from amount compare capacity and qualitative jump executive function and reasoning.